Capital requirements, disclosure, and supervision in the European insurance industry : new challenges towards Solvency II - Starita, Maria Grazia; Malafronte, Irma; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Capital Requirements, Disclosure, and Supervision in the European Insurance Industry provides an in-depth analysis of Solvency II's issues by combining both a theoretical approach and evidence of the empirical implications and effects on the European insurance industry.
Keywords: Insurance -- Europe; Insurance -- State supervision -- Europe; Working capital -- Europe; Capital -- Europe